Beyond Argumentum in Terrorem: The Contested Rhetoric of Campus Carry - Albion M. Butters (Cambridge University Press & British Association for American Studies, 2022)
This essay reflects on the use of competing rhetorical frames of fear strategically used by the academic community of The University of Texas at Austin in the debate on Campus Carry policy. With the legalization of concealed handguns on campus, fear emerged as a prominent trope in public discussions, albeit used in very different ways by supporters or opponents of the law. Against the more standard interpretation of fear-based rhetoric as an exploitation of others’ insecurities, this essay draws on mixed-methods research to examine expressions of fear by activist opponents of Campus Carry and the way in which supporters of the law sought to deconstruct it.